Analisis Faktor-Faktor Komplain Yang Mempengaruhi Klaim Nasabah pada PT. Sunlife Finansial Cabang Medan - Lubis, Tasya Fauza; Syahriza, Rahmi (Universitas Labuhanbatu, 2021)
This study aims to analyze the complaints factors that affect customer claims at PT. Sunlife Financial Medan branch. This research was conducted to find out the causes of complaints to customers, to find out the forms and types of complaints that occurred to customers. This research data uses descriptive and qualitative methods which include collecting data, conducting interviews and conducting observations. from the results of this study it will be found the factors that cause complaints of claims that occur to customers at PT. Sunlife financial Medan branch.